Systems analysis & design - Low, Kok Han (Cengage Learning Asia, 2012)
Great effort has been invested in writing a book which introduce readers to fundamental areas of system analysis and design. This book can be used as a foundation for analysis and design of systems in a programme, Computer Science and IS. It is suitable for students who are pursuing a basic course in these areas for the very first time.